Early-Life Host–Microbiome Interphase: The Key Frontier for Immune Development - Amenyogbe, Nelly; Kollmann, Tobias R.; Ben-Othman, Rym (Frontiers in Pediatrics, 2017)
Human existence can be viewed as an ‘animal in a microbial world’. A healthy interaction of the human host with the microbes in and around us heavily relies on a well-functioning immune system. As development of both the microbiota and the host immune system undergo rapid changes in early life, it is not surprising that even minor alterations during this co-development can have profound consequences. Scrutiny of existing data regarding pre-, peri- as well as early post-natal modulators of newborn microbiota indeed suggest strong associations with several immune mediated diseases with onset far beyond the newborn period. We here summarize this data and extract overarching themes. This same effort in turn sets the stage to guide effective counter-measures, such as probiotic administration. The objective of our review is to highlight the interaction of host immune ontogeny with the developing microbiome in early life as a critical window of susceptibility for life long disease, as well as to identify the enormous potential to protect and promote life long health by specifically targeting this window of opportunity.